Gene Targets in Ocular Pathogenic Escherichia coli for Mitigation of Biofilm Formation to Overcome Antibiotic Resistance - Ranjith, Konduri; Ramchiary, Jahnabi; Prakash, Jogadhenu S. S.; Arunasri, Kotakonda; Sharma, Savitri; Shivaji, Sisinthy (Frontiers in Microbiology, 2019)
The present work is an attempt to establish the functionality of genes involved in biofilm formation and antibiotic resistance in an ocular strain of E. coli (L-1216/2010) which was isolated and characterised from the Vitreous fluid of a patient with Endophthalmitis. For this purpose, seven separate gene-specific knockout mutants were generated by homologous recombination in ocular Escherichia coli. The genes that were mutated included three transmembrane genes ytfR (ABC transporter ATP-binding protein), mdtO (multidrug efflux system) and tolA (inner membrane protein), ryfA coding for non-coding RNA and three metabolic genes mhpA (3-3-hydroxyphenylpropionate 1,2-dioxygenase), mhpB (2,3-di hydroxyphenylpropionate 1,2-dioxygenase) and bdcR (regulatory gene of bdcA). Mutants were validated by sequencing and Reverse transcriptase-PCR and monitored for biofilm formation by XTT method and confocal microscopy. The antibiotic susceptibility of the mutants was also ascertained. The results indicated that biofilm formation was inhibited in five mutants (ΔbdcR, ΔmhpA, ΔmhpB, ΔryfA and ΔtolA) and the thickness of biofilm reduced from 17. 2 µm in the wildtype to 1.5 to 4.8 µm in the mutants. Mutants ΔytfR and ΔmdtO retained the potential to form biofilm. Complementation of the mutants with the wild type gene restored biofilm formation potential in all mutants except in ΔmhpB. The 5 mutants which lost their ability to form biofilm (ΔbdcR, ΔmhpA, ΔmhpB, ΔtolA and ΔryfA) did not exhibit any change in their susceptibility to Ceftazidime, Cefuroxime, Ciprofloxacin, Gentamicin, Cefotaxime, Sulfamethoxazole, Imipenem, Erythromycin and Streptomycin in the planktonic phase compared to wild type ocular E. coli. But ΔmdtO was the only mutant with altered MIC to Sulfamethoxazole, Imipenem, Erythromycin and Streptomycin both in the planktonic and biofilm phase. This is the first report demonstrating the involvement of the metabolic genes mhpA and mhpB and bdcR (regulatory gene of bdcA) in biofilm formation in ocular E. coli. In addition we provide evidence that tolA and ryfA are required for biofilm formation while ytfR and mdtO are not required. Mitigation of biofilm formation to overcome antibiotic resistance could be achieved by targeting the genes bdcR, mhpA, mhpB, ryfA and tolA.